Kwetsbaarheid in een veerkrachtige samenleving. Een socio-institutionele analyse van de graancrisis van 1480-82. Casus: Gierle in het Land van Turnhout - Van den Broeck, Nick; Soens, Tim (TSEG - The Low Countries Journal of Social and Economic History, 2017)
Food crises in the premodern period are often explained by focusing on weather- or climate- related harvest failures (Food Availability Decline) or market disturbances provoking a declining access to food for some groups in society (Food Entitlement Decline). However, the FAD versus FED –debate does not fully acknowledge the underlying mechanisms which expose people to hunger. With this contribution, we aim to move the focus in historical famine research back to the vulnerabilities in the means of subsistence enjoyed by particular groups in a society and the way these vulnerabilities are continuously produced through inequalities in the access to land, labour and capital, and through the organisation and allocation of taxes and feudal rent. Inequalities in wealth and income resulted in social differences in the access to food, which were far more important than fluctuations over time produced by climate shocks or market disturbance. As a result even in an overall resilient society as the fifteenth century Campine Area in the Duchy of Brabant, a large proportion of the population was structurally vulnerable to hunger